2015
DOI: 10.3390/ijerph120100692
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Environmental Tobacco Smoke Exposure of Preschool Children: A Randomized Controlled Trial of Class-Based Health Education and Smoking Cessation Counseling for Caregivers

Abstract: Objectives: To assess counseling to caregivers and classroom health education interventions to reduce environmental tobacco smoke exposure of children aged 5–6 years in China. Methods: In a randomized controlled trial in two preschools in Changsha, China, 65 children aged 5–6 years old and their smoker caregivers (65) were randomly assigned to intervention (n = 33) and control (no intervention) groups (n = 32). In the intervention group, caregivers received self-help materials and smoking cessation counseling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In Wahabi et al's study the mean birth weight of infants of exposed mothers was significantly lower by 35 g, mean birth weight of infants of exposed compared to the infants of unexposed mothers [3].Results of our study denoted that 73.7% of all participants, 74.2% of active smokers and 81.2% of smokers during pregnancy agreed to the statement that -There is a relationship between the smoking during pregnancy and low birth weight‖.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In Wahabi et al's study the mean birth weight of infants of exposed mothers was significantly lower by 35 g, mean birth weight of infants of exposed compared to the infants of unexposed mothers [3].Results of our study denoted that 73.7% of all participants, 74.2% of active smokers and 81.2% of smokers during pregnancy agreed to the statement that -There is a relationship between the smoking during pregnancy and low birth weight‖.…”
Section: Resultssupporting
confidence: 73%
“…Active smoking and environmental tobacco smoke (ETS) exposure is one of the most important preventable cause of disease and premature death [1].ETS classified as Group A carcinogen by United States Environmental Protection Agency and consists of two components including second-hand tobacco smoke (SHS) and third-hand tobacco smoke (THS) [2][3][4][5]. The mixture of smoke emitted by the smoker's breath and the smoke resulting from the combustion of cigarettes or other tobacco products is called as SHS [1,6].An important part of smoke in indoor environments adheres to the hair, skin, or clothes of smokers, furniture, floors, walls, bedding, carpets, dust and other surfaces and may remain for a long time on these surfaces and this remains considered as THS [5].These residuals can be re-emitted into the gas phase, or react with the oxidants in the environment to produce further pollutants [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Three additional studies in P/C smokers with young children <6 years of age reported some success with P/C cessation and a decrease in children's TSE; however, all studies used self-report and lacked biochemical verification of cessation outcomes. [16][17][18] In a study with children <4 years old whose mothers were smokers, both mothers' self-report and bioverified 7-day point prevalence quit rates 19 were used. Also, a pilot study was conducted in which researchers educated nonsmoking adolescents in an effort to encourage their Ps/ Cs to quit smoking.…”
mentioning
confidence: 99%
“…A caregiver completed a structural questionnaire, which had previously indicated 100% response rate and good validation ( 17 ) to collect information about their smoking behavior. This information was collected from everyone living with a child and included smoking (yes/no), and the number of cigarettes smoked at home.…”
Section: Methodsmentioning
confidence: 99%